DIMENSI METAVERSE DALAM NOVEL DAN SERIAL ANIME SWORD ART ONLINE: KAJIAN EKRANISASI - Adi Suryo Nugroho; Titik Maslikatin; Sunarti Mustamar; Zahratul Umniyyah (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2023)
Reki Kawahara's Sword Art Online novels have been ecranized into a television anime series, going from four volume novels to 25 episodes. However, in this article the material object is a twovolume novel which is ecranized into 14 episodes. This research using qualitative method aims to understand the changes that occur from the novel version to the television series version by using the theory of ecranization. The results of the study show that in the ecranization process there are three changes, namely shrinking, adding, and varying changes. These three changes had positive impacts, including the sequencing of episodes which made it easier for viewers who had not read the novel version to understand, and the television series version could be enjoyed by more viewers. The novels and television series Sword Art Online provide an overview of the metaverse technology created by Mark Zuckerberg by combining the real and virtual worlds. The work has affinities with metaverse concepts such as 3D virtual space, avatars, and full immersion. However, the sophistication of this technology has received criticism because it has the potential to cause addiction to the virtual world.